The Littles : story and pictures - Peterson, John Lawrence, 1924- (New York : Scholastic, 1968)
A family of tiny people experiences a crisis when a baby is born during a snowstorm.
G3
Keywords: Little family (Fictitious characters) -- Fiction; Fantasy